2001
DOI: 10.1159/000047101
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate in Cerebral Tissue of Asphyxiated Neonates during the First Week of Life Demonstrated in vivo Using Proton Magnetic Resonance Spectroscopy

Abstract: We tested the hypothesis that glutamate (Glx) levels as demonstrated by proton magnetic resonance spectroscopy (1H-MRS) are elevated in brain tissue of neonates with severe hypoxic-ischemic encephalopathy (HIE). Studies were performed in 26 neonates (median gestational age 40.5 weeks, range 36.7–42.4 weeks; median birth weight 3,360 g, range 2,180–4,200 g). The median postnatal age at the time of testing was 2.5 days (range 1–7 days). HIE was scored according to Sarnat as grade I (n = 4), grade II (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In this case, energy failure will lead to neuronal cell death. The Glu/NAA ratio has been found closely related to excitotoxic brain damage in infants, and hypothermia has been shown to reduce the Glu/NAA ratio already at 6 hours post hypoxia in newborn piglets [ 27 , 28 ]. This is consistent with our findings of significantly reduced Glu/NAA in both cortex and hippocampus of hypothermic piglets (Figs 2 and 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, energy failure will lead to neuronal cell death. The Glu/NAA ratio has been found closely related to excitotoxic brain damage in infants, and hypothermia has been shown to reduce the Glu/NAA ratio already at 6 hours post hypoxia in newborn piglets [ 27 , 28 ]. This is consistent with our findings of significantly reduced Glu/NAA in both cortex and hippocampus of hypothermic piglets (Figs 2 and 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the high concentration and activity of glutamate receptors aggravate the deleterious effects of this excitatory amino acid in the immature brain (Johnston et al, 2011 ; Drury et al, 2014 ; Juul and Ferriero, 2014 ). Among various approaches to quantify the increase in glutamate content in the immature brain after a hypoxic-ischemic insult, the Glu/NAA ratio has been observed to be closely related to excitotoxic brain damage (Groenendaal et al, 2001 ). The relative paucity of antioxidants and excess of pro-oxidant substances (in particular, iron) determine the particular susceptibility of the immature brain to oxidative stress (Johnston et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, proton spectra were localized to the basal ganglia because previous studies using MRI have identified this area as vulnerable to hypoxia-ischemia injury in neonates (19). Spectra from this region are also less susceptible to interference arising from extracranial fat tissue (20).…”
Section: Discussionmentioning
confidence: 99%